The witches of St. Petersburg : a novel - Edwards-Jones, Imogen (Harper, 2019)
Inspired by real characters, this transporting historical fiction debut spins the fascinating story of two princesses in the Romanov court who practiced black magic, befriended the Tsarina, and invited Rasputin into their lives-forever changing the course of Russian history.